Performance enhancements in poly(vinylidene fluoride)-based piezoelectric nanogenerators for efficient energy harvesting. (February 2019) - Yan, Jing; Liu, Min; Jeong, Young Gyu; Kang, Weimin; Li, Lan; Zhao, Yixia; Deng, Nanping; Cheng, Bowen; Yang, Guang
Abstract: A great progress has been made in the field of energy harvesting over the past few years to meet the ever-increasing desire of portable, sustainable and renewable energies. Corresponding devices are designed to capture the ambient energies and convert them into usable electrical energy. Piezoelectric nanogenerator, directly scavenging a wide variety of limitless mechanical energy, has been considered as an attractive alternative over traditional rechargeable batteries for providing electrical power to various electric devices. Among piezoelectric materials, poly(vinylidene fluoride) (PVDF) and its copolymers are the most promising candidates for piezoelectric nanogenerators due to their unique electroactive properties, high flexibility, good processability, and long-term stability. However, the piezoresponse generated from their nanogenerators is still low and cannot drive most of electronic devices. Tremendous efforts have been committed to promote the technology and enhance the performance of PVDF-based piezoelectric nanogenerators. This review article highlights recent advances in their performance enhancements with fabrication techniques, piezoelectric materials, conductive and non-conductive fillers. These advanced techniques, new designs and functional materials will be helpful for the increase of piezoelectric crystal structures, alignment of dipoles, charge transfer, etc ., consequently improving the output performance of piezoelectric devices. Finally, some perspectives and challenges in this field are also discussed. This comprehensive review will help researchers to learn the piezoelectricity of PVDF-based materials for efficiently converting mechanical energy into electricity, which eventually leads PVDF-based nanogenerators to be a practical power source. Graphical abstract: Highlights: Recent progress of PVDF piezoelectric nanogenerators is summarized. Advanced fabrication techniques and loading of additives are applied to enhance piezoelectric performance. The working mechanisms of performance enhancements of nanogenerators are proposed. An insightful perspective is outlined for the future research.